THE EFFECT OF ASSIGNMENT DELIVERY METHODS ON STUDENT MOTIVATION IN STOICHIOMETRY LEARNING. - Suleman (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2025)
ABSTRACT The issue addressed in this research is the influence of task assignment methods on student learning motivation in the topic of Stoichiometry. Task assignment methods refer to a teaching strategy in which instructors provide tasks outside of class hours, aimed at developing students' independence in reading and understanding the concepts taught. The assignment of tasks is expected to impact students' learning motivation in comprehending Stoichiometry concepts. Student motivation has a significant effect on improving academic performance. This research investigates the influence of task assignment methods on student learning motivation in the context of Stoichiometry. This study is a quantitative experimental research. The sampling technique used in this study is random sampling, with a sample size of 17 students from the odd semester. Data collection was performed using questionnaires, test results, and documentation. Based on hypothesis testing using a paired sample t-test, the results indicated that there is an influence of the task assignment method on students’ learning motivation in the Stoichiometry topic. The independent sample t-test calculation showed a significance value of 0.000 < 0.05, thus rejecting the null hypothesis (H₀), which means that there is a significant effect of the task assignment method on student learning motivation in Stoichiometry.